2013
DOI: 10.1371/journal.pone.0068784
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Both EGFR and IGF1R Sensitized Prostate Cancer Cells to Radiation by Synergistic Suppression of DNA Homologous Recombination Repair

Abstract: Reduced sensitivity of prostate cancer (PC) cells to radiation therapy poses a significant challenge in the clinic. Activation of epidermal growth factor receptor (EGFR), type 1 insulin-like growth factor receptor (IGF1R), and crosstalk between these two signaling pathways have been implicated in the development of radiation resistance in PC. This study assessed the effects of targeting both receptors on the regulation of radio-sensitivity in PC cells. Specific inhibitors of EGFR and IGF1R, Erlotinib and AG102… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…DNA damage and enhanced DNA repair [41]. Inhibition of IGF-1R resulted in the delayed repair of radiation-induced DNA doublestrand breaks, potentiating the antiproliferative effect of radiation therapy [42,43]. IGF-1R signaling was also involved in resistance to conventional chemotherapy [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage and enhanced DNA repair [41]. Inhibition of IGF-1R resulted in the delayed repair of radiation-induced DNA doublestrand breaks, potentiating the antiproliferative effect of radiation therapy [42,43]. IGF-1R signaling was also involved in resistance to conventional chemotherapy [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, IGF1R can physically associate with EGFR, and the ligands EGF and IGF1 can activate both EGFR and IGF1R even when the two receptors are not physically connected (58)(59)(60)(61). Since LMP1 regulates activation of EGFR and IGF1R, it is possible that LMP1 promotes interaction between these receptors to facilitate their phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…These structural homologous receptors are recognized for tumor cell regulation of proliferation, survival, apoptosis, and angiogenesis [28, 29] making these two receptors favorable targets for cancer therapy [24, 29, 30]. Recent studies have shown IGF1R mainly mediates via the PI3K/AKT pathway while the EGFR mediates through the Ras/MAP kinase pathway [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown selective inhibition of one receptor will lead to compensatory and enhanced activation of the other receptor axis [29, 33, 34]. These cellular and molecular mechanistic observations have led to research on specific targeted therapy for dual inhibition of EGFR and IGF1R [2830, 35]. …”
Section: Discussionmentioning
confidence: 99%